2016
DOI: 10.3390/microorganisms4030025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Procedures to Detect Chlamydia trachomatis Infections

Abstract: The intracellular life style of chlamydia and the ability to cause persistent infections with low-grade replication requires tests with high analytical sensitivity to directly detect C. trachomatis (CT) in medical samples. Nucleic acid amplification tests (NAATs) are the most sensitive assays with a specificity similar to cell culture and are considered the method of choice for CT detection. In addition, NAATs can be performed on various clinical specimens that do not depend on specific transport and storage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 53 publications
1
117
0
8
Order By: Relevance
“…Chlamydia are auxotrophic for tryptophan and respond to this stress situation with generation of morphological aberrant, non‐replicative, persistent forms that presumably convert into replicative forms as environmental conditions improve (Bastidas, Elwell, Engel, & Valdivia, ). As for C. trachomatis (Meyer, ), which is phylogenetically highly related to C. suis , persistent C. suis infections most likely are associated with a positive antibody response, and thus, negative serology may assist to rule out the involvement of chlamydia. In addition, as for C. trachomatis (Meyer, ), low‐grade replication possibly also occurs during chronic C. suis infections and serology might be useful in the diagnostic work‐up of such suspected chronic infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydia are auxotrophic for tryptophan and respond to this stress situation with generation of morphological aberrant, non‐replicative, persistent forms that presumably convert into replicative forms as environmental conditions improve (Bastidas, Elwell, Engel, & Valdivia, ). As for C. trachomatis (Meyer, ), which is phylogenetically highly related to C. suis , persistent C. suis infections most likely are associated with a positive antibody response, and thus, negative serology may assist to rule out the involvement of chlamydia. In addition, as for C. trachomatis (Meyer, ), low‐grade replication possibly also occurs during chronic C. suis infections and serology might be useful in the diagnostic work‐up of such suspected chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…As for C. trachomatis (Meyer, ), which is phylogenetically highly related to C. suis , persistent C. suis infections most likely are associated with a positive antibody response, and thus, negative serology may assist to rule out the involvement of chlamydia. In addition, as for C. trachomatis (Meyer, ), low‐grade replication possibly also occurs during chronic C. suis infections and serology might be useful in the diagnostic work‐up of such suspected chronic infections. However, serology is inappropriate for immediate diagnosis of acute C. suis infections as convalescent sera are needed to this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…[63] Other nucleic acid detection/amplification tests such as gene probe assay, loop-mediated isothermal amplification assay, ligase chain reaction assay, and strand displacement amplification have been tried or are under development for C. trachomatis detection, but none are used routinely. [64]…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…However, serology may be helpful in the diagnosis of chronic and invasive infections such as LGV. [64] Later, it was observed that the antibodies against Chlamydophila pneumoniae are highly cross-reactive with C. trachomatis antibodies. Therefore, it became clear that the exact prevalence of C. trachomatis infection cannot be easily determined from antibody detection.…”
Section: Role Of Serology In Laboratory Diagnosismentioning
confidence: 99%
“…Во-вторых, ввиду того, что постановка диагноза хламидийной инфекции требует проведения интенсивного курса антибиотикотерапии, часто с использованием нескольких препаратов, при диагностике урогенитального хламидиоза необходимо использовать не менее 2-х методов, отвечающих требованиям строгой специфичности и чувствительности. Одним из таких методов является ПЦР, который должен быть подтвержден методом иммунодетекции возбудителя [3,4]. И, в-третьих, в последнее время в связи с актуальностью контроля за распространением хламидийной инфекции особое значение приобретает разработка быстрых скрининговых тестов, что позволит поставить диагноз и начать лечение уже после первого обследования пациента, так называемые "point of care" (РОС) тесты.…”
Section: Introductionunclassified